LNN-Powered Logic Bomb Detection of RCE Vulnerabilities in Registry Activity for Windows 11 - A Case Study - Jaimin Jani (International Journal of Intelligent Systems and Applications in Engineering, 2024)
The prevalence of Remote Code Execution (RCE) vulnerabilities endangers the security of modern computing systems, especially when used in complex attack vectors like logic bombs. These malicious scripts, which are frequently embedded within normal processes, use registry activity to perform damaging activities under specified conditions. This study describes a unique way to detecting logic bomb activities using Liquid Neural Networks (LNN) in the context of Windows 11 registry activity. Our LNN model effectively detects unusual patterns that indicate potential RCE exploits by continuously monitoring and analyzing registry changes. The paper describes how to acquire registry activity data, extract features, and then train the LNN model. Through thorough testing, our technique exhibits a high detection accuracy, delivering a strong solution for preventive identification. The study uses Liquid Neural Networks (LNN) to discover and signal harmful modifications that may indicate logic bombs.